2021
DOI: 10.1038/s41573-021-00189-2
|View full text |Cite
|
Sign up to set email alerts
|

Navigating CAR-T cells through the solid-tumour microenvironment

Abstract: The adoptive transfer of T cells that are engineered to express chimeric antigen receptors (CARs) has shown remarkable success in treating B-cell malignancies but only limited efficacy against other cancer types, especially solid tumours. Compared with haematological diseases, solid tumours present a unique set of challenges, including a lack of robustly expressed, tumour exclusive antigen targets as well as highly immunosuppressive and metabolically challenging tumour microenvironments, that limit treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
202
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(244 citation statements)
references
References 237 publications
0
202
0
1
Order By: Relevance
“…Thus, the same configuration should be considered when similar results are seen in future investigations of PTK7-CAR T-cell's toxicity profiles; alternatively, tuning scFv affinity and/or concomitantly integrating different co-stimulatory domains may ameliorate the potential concern of on-target off-tumor effect as typical representation for CAR T-cell therapy targeting a range of different antigens including but not limited to HER2, EGFR, CD38 (8,51,52). Given the above inherent risks, multiple inducible safety controls that can be built into or applied in conjunction with CAR-T cells should be considered, such as inducible caspase 9 (iCasp9) or tEGFR tag as we integrated in CAR design where tEGFR-expressing CAR-T can be depleted by commercially available antibody cetuximab in case of emergent side effects (53). In sum, further thorough investigations are definitely needed to fully explore the potential toxicities of PTK7-CAR T cells before translating into clinic by using PTK7-CARs with cross-reactivity in mouse and even non-human primate models.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the same configuration should be considered when similar results are seen in future investigations of PTK7-CAR T-cell's toxicity profiles; alternatively, tuning scFv affinity and/or concomitantly integrating different co-stimulatory domains may ameliorate the potential concern of on-target off-tumor effect as typical representation for CAR T-cell therapy targeting a range of different antigens including but not limited to HER2, EGFR, CD38 (8,51,52). Given the above inherent risks, multiple inducible safety controls that can be built into or applied in conjunction with CAR-T cells should be considered, such as inducible caspase 9 (iCasp9) or tEGFR tag as we integrated in CAR design where tEGFR-expressing CAR-T can be depleted by commercially available antibody cetuximab in case of emergent side effects (53). In sum, further thorough investigations are definitely needed to fully explore the potential toxicities of PTK7-CAR T cells before translating into clinic by using PTK7-CARs with cross-reactivity in mouse and even non-human primate models.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their high targeting and powerful antitumor activity, CAR-T cells are widely used in research and the treatment of various cancers. Recently, researchers have also extended CAR-T therapy to solid tumors, including OS [20][21][22]. Furthermore, related studies have reported that adoptively transferred effector cells derived from naive T cells mediate superior antitumor effects, and youth carry more naive cells [124,125].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these encouraging results, the Food and Drug Administration (FDA) recently approved two CAR-T cells targeting the CD19 protein for the treatment of acute lymphoblastic leukemia and diffuse large B-cell lymphoma [19]. Recently, researchers have also extended CAR-T therapy to solid tumors, including OS [20][21][22]. Koksal et al summarized CAR-T-cell therapy for OS several years ago [22].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we evaluated the delivery of engineered T cells in our model. Chimeric antigen receptor (CAR) T cells have been heavily investigated in treating solid tumors in recent years [50]. CAR T cells have to arrest on and penetrate through the endothelium, which negatively regulate T cell functions [51], before reaching the cancer cells expressing the tumor (associated) antigens.…”
Section: Molecular and Cellular Deliveries Can Be Tracked In The Vascularized Tumor Modelmentioning
confidence: 99%